Synthesis and characterisation of Zinc/Aluminium-Layered Double Hydroxide-L-Phenylalanate Nanocomposites using ION exchange method - Mohd Sharif Sharifah Norain, Hashim Norhayati, Md Isa Illyas, Mohd Ali Noorshida, Muhamad Damanhuri Muhd Ibrahim, (Universiti Pendidikan Sultan Idris, 2017)
Synthesis and characterisation of Zinc/Aluminium-Layered Double Hydroxide-L-Phenylalanate Nanocomposites using ION exchange method by Mohd Sharif Sharifah Norain, Hashim Norhayati, Md Isa Illyas, Mohd Ali Noorshida, Muhamad Damanhuri Muhd Ibrahim,